Teknik Kultur Embrio Jagung (Zea mays L.) melalui Modifikasi Media Kultur Jaringan - Elea Nur Aziza; Annisa Khoiriyah; Geraldo Adinugra Rimartin; Sari Megawati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study explores the use of embryo culture as a strategic approach to rescue maize (Zea mays L.) embryos derived from interspecific crosses that fail to develop normally. Not all crosses result in viable seeds; in many cases, embryos remain immature or undergo developmental arrest, which increases the risk of embryo abortion before they can develop into complete plants. Embryo development failure in maize crosses, especially in combinations involving genetically distant genotypes, represents a major constraint in plant breeding programs. Without appropriate intervention, the resulting hybrid genotypes may be lost and consequently slow down the development of new superior varieties. To address this limitation, immature embryo culture represents an effective in vitro technique. Embryo culture involves the excision of young or incompletely developed plant embryos from seeds or ovaries and their subsequent cultivation on nutrient-rich artificial media to support further growth and plant regeneration. The objective of this study was to identify the optimal Murashige and Skoog (MS)-based culture medium composition for immature maize embryo growth using a factorial completely randomized design with three replications. Treatments consisted of combinations of agar concentration (4, 6, 8, and 10 g L⁻¹) and medium strength (0.5 MS, 0.75 MS, and 1 MS). The results indicated no significant interaction between MS medium strength and agar concentration. 1 MS medium produced the best results for shoot height, root length, and root number, whereas 0.75 MS medium resulted in the highest germination percentage. No significant differences were observed among treatments for days to germination and leaf number. An agar concentration of 6 g L⁻¹ yielded the highest germination percentage and shoot height, while other variables were not significantly affected by agar concentration. In conclusion, 1 MS medium or an agar concentration of 6 g L⁻¹ can be recommended for the culture of immature maize embryos